Conditional Power Monitoring of Domestic Loads through Human Machine Interface - John Wiselin, M. C.; Aravind, C. V.; Kumar, Rajparthiban; Sugendran (Asian Journal of Electrical Sciences, 2013)
A real time data acquisition system for load monitoring using human machine interface is presented. The design proposes a real time data acquisition whose parametric values are monitored and recorded for analysis purposes in a typical power system set-up. The parametric measurements includes the load voltage, load current, active power, reactive power, apparent power, power factor and line current. A perfect interface design is developed using graphical system design software. The recorded data is highly helpful in power monitoring and analysis for performance evaluation. The design gets complete with a manual supervisory control based on the data acquired through the interface module.